2020
DOI: 10.1177/0036933020949228
|View full text |Cite
|
Sign up to set email alerts
|

Is routine colonoscopy necessary for patients who have an unequivocal computerised tomography diagnosis of acute diverticulitis?

Abstract: Aims To assess the incidence of underlying colorectal malignancy in patients admitted as an emergency with a CT diagnosis of acute diverticulitis and determine the need for routine follow up colonoscopy Methods A retrospective study was performed on all patients who had been admitted to our surgical unit with CT diagnosed diverticulitis from September 2016 to September 2018 (n = 125). Results 11 patients (8.8%) required emergency resection with no underlying malignancy found. 76 patients (61%) had a follow up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A total of 68 studies with 13 905 patients were included 6,24–90 . There were four prospective studies and one retrospective review of a prospective study 44,60,61,77,89 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 68 studies with 13 905 patients were included 6,24–90 . There were four prospective studies and one retrospective review of a prospective study 44,60,61,77,89 .…”
Section: Resultsmentioning
confidence: 99%
“…There were 13 296 patients from 65 studies who underwent a follow up colonoscopy 6,24–42,44–65,67–79,81–90 . The remaining three studies (231 patients) reported follow up with either a colonoscopy or flexible sigmoidoscopy and did not differentiate between the two 43,66,80 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, we continue to publish articles on Covid-9 pandemic, 6 there is urgent need for us to establish a balance of continuity with publication of non-covid urgent research. Whether that is related to diagnostic test 7,8 or basic research aimed at understanding molecular aspects of drug action 9 or novel innovation in treatment. 10 All that is responsibility of any peerreviewed multidisciplinary journal such as SMJ.…”
mentioning
confidence: 99%